Maritime Academy to Receive $1.2 Million - Vallejo News Chronicle (Vallejo News Chronicle)
Gov. Edmund G. Brown's 1959-60 budget includes $442,145 for operation of the California Maritime Academy near Vallejo, and $763,800 for capital outlay construction projects.